Description of Breakfast Habits, Nutritional Status and Level of Achievement of Al-Huda Madrasah Ibtidaiyah Kep uhbener Nganjuk District - Fika Nur Septianingtias; Juliana Christyaningsih; Annas Buanasita; Nur Hatijah (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Breakfast is very important for elementary school children because with breakfast, the nutritional needs for their activities while at school can be fulfilled, with the fulfillment of nutritional needs. The purpose is to know the description of breakfast habits, breakfast intake, nutritional status and level of learning achievement at MI Al-Huda Kepuh Bener, Nganjuk Regency. Research method is descriptive using a proportional random sampling technique. The way to collect data is by means of anthropometric measurements, interviews using questionnaires, food recall interviews 3 times breakfast, observation of odd semester student report cards. It was obtained data on nutritional status based on (BMI/Age) as many as (76.9%) students had good nutritional status, (66.7%) had sufficient breakfast habits, (38.5%) had a deficit energy consumption level weight, (56.3%) had a deficit consumption level of protein intake and as many as (89.7%) had a good level of academic achievement. Concluded that most students have normal nutritional status, students who have good breakfast habits but a deficit consumption level, students have a deficit consumption level but a good level of learning achievement. It is recommended for students to eat a balanced diet and get used to breakfast